Post-socialist transition and the intergenerational transmission of education in Kyrgyzstan - Tilman Brück; Damir Esenaliev (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
We investigate long-term trends in the intergenerational transmission of education in a low income country undergoing a transition from socialism to a market economy. We draw on evidence from Kyrgyzstan using data from three household surveys collected in 1993, 1998 and 2011. We find that Kyrgyzstan, like Eastern European middle income transition economies, generally maintained high educational mobility, comparable to the levels during Soviet times. However, we find that the younger cohorts, who were exposed to the transition during their school years, experienced a rapid decline in educational mobility. We also document that gender differences in schooling and educational mobility, found among older-aged individuals, disappeared in the younger population.
Keywords: J62; P36; I25; 330; intergenerational mobility; educational attainment; gender; transition economy; Kyrgyzstan; Central Asia